2002
DOI: 10.1017/s0272263102002103
|View full text |Cite
|
Sign up to set email alerts
|

Input-Driven Language Learning

Abstract: Input-driven models provide an explicit and readily testable account of language learning. Although we share Ellis's view that the statistical structure of the linguistic environment is a crucial and, until recently, relatively neglected variable in language learning, we also recognize that the approach makes three assumptions about cognition and language learning that are not universally shared. The three assumptions concern (a) the language learner as an intuitive statistician, (b) the constraints on what co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 34 publications
1
12
0
Order By: Relevance
“…In terms of language input, the finding of this current study is consistent with the result of a study conducted by Harrington and Dennis (2002). The result of their investigation of input-driven in second language learning indicated that task frequency played an essential role in the acquisition of the second language (Wang, 2010).…”
Section: Features Of Language Inputsupporting
confidence: 90%
See 1 more Smart Citation
“…In terms of language input, the finding of this current study is consistent with the result of a study conducted by Harrington and Dennis (2002). The result of their investigation of input-driven in second language learning indicated that task frequency played an essential role in the acquisition of the second language (Wang, 2010).…”
Section: Features Of Language Inputsupporting
confidence: 90%
“…Most scholars and researchers in the area of second language acquisition justify that the three variables above have a significant contribution in developing EFL learners' language acquisition. A study conducted by Harrington and Dennis (2002), taking into account language input, concluded that the task frequency played an essential role in the input-driven approach and language learning process. It indicates that pre-modified input by utilizing frequency task significantly facilitates the EFL learners' comprehension.…”
mentioning
confidence: 99%
“…To be sure, the APT escapes the considerable induction problem facing input-driven approaches by assuming UG as a direct constraint on learning (Harrington and Dennis, 2002). But the a priori assumption of a guiding role in learning for these abstract linguistic principles is at fundamental odds with the aims and the logic of the CM approach.…”
Section: Learningmentioning
confidence: 99%
“…As noted earlier, polysemous words tend to be highly frequent. Frequency is important for both individual experiences (such as task frequency) and linguistic experiences (distributional frequency; Harrington & Dennis, 2002). In consideration of linguistic experiences, frequency is important not only for lexical acquisition but also for the acquisition of syntax, phonology, and morphology.…”
Section: Introductionmentioning
confidence: 99%